1993
DOI: 10.1258/002367793780745606
|View full text |Cite
|
Sign up to set email alerts
|

A simple technique for blood collection in the pig

Abstract: SummaryA simple technique for blood collection in pigs of body weight 15-40 kg is described. The subcutaneous abdominal vein was used for rapid collection of 5-20 ml of blood samples. The animals were premedicated with 10 mg/kg of ketamine and 600 ",g of atropine given intramuscularly prior to blood collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…4 Swine were sedated prior to sampling, and a 19-to 21-gauge needle was used. A technique has been described 5 for IV catheter implantation in the subcutaneous abdominal vein in adult domestic swine. Results of the study indicated that there are few permanent sequelae to subcutaneous abdominal vein catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…4 Swine were sedated prior to sampling, and a 19-to 21-gauge needle was used. A technique has been described 5 for IV catheter implantation in the subcutaneous abdominal vein in adult domestic swine. Results of the study indicated that there are few permanent sequelae to subcutaneous abdominal vein catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…All animals were surgically implanted with vascular-access catheters to permit collection of serial blood samples and for medication administration (e.g., analgesics, antibiotics if necessary) postoperatively. Porcine animal models pose a special challenge for long-term vascular access given their size and lack of physical restraint [ 22 ]-[ 24 ]. Catheters were initially placed in the external jugular vein percutaneously, but early problems with this technique led us to switch to tunneled placement in the internal jugular vein under anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Several techniques for placing intravenous catheters in pigs have been described in the scientific literature. [5][6][7][8][9][10][11][12] Although intravenous catheterization of 8-and 10-week-old pigs is routinely conducted in different research facilities, such catheterization in neonatal and younger pigs is challenging. Moreover, most research papers reporting the use of intravenous catheters in these age categories do not provide adequate details of the catheterization protocol, limiting the ability of other researchers to adopt these techniques.…”
mentioning
confidence: 99%